Discursive Construction of the "Other" in the New World Order - Lazar, Annita (Universiti Putra Malaysia Press, 2014)
4th Malaysian International Conference on Languages, Literatures and Cultures (MICOLLAC) on ‘Critical Perspectives on Theory and Practice in the New World Order’